Innovation in how to present a lesson on traditional persian medicine: explaining the experiences of medical students - Fatemeh Eghbalian; Hoorieh Mohammadi; Amir Hossein Jamshidi; Mansoureh Taghavinia (BMC Medical Education)
Abstract Background World Health Organization has advised countries to integrate modern medicine with approved Traditional Medicine and Complementary and Alternative Medicine services in their health system, and it uses for prevention and treatment. The study, conducted aim to explain the experiences of medical students after completing the mentioned one-week course. Methods This study was qualitative and qualitative content analysis of the data was conducted using the approach of Graneheim and Lundman, which includes six stages. Semi-structured written interviews with a main open question (please write your experience regarding the one-week courses of familiarization with Persian Medicine, considering before and after the course) were used as the primary method for data collection. MAXQDA10 software was used for data management and initial coding. A total of 20 individuals participated in this study. Results The experiences of medical students participating in the traditional medicine course were categorized into two themes include outcomes of medical students’ participation in the Traditional Persian medicine course and influencing and hindering factors the conduct of the Persian medicine course. Conclusions If, course planning is rewritten in such a way that is removed repetitive and non-useful items. It can be concluded that one week is a relatively suitable time to present a Traditional Persian Medicine lesson. Medical students declared it necessary to continue holding the course due to the need they will have knowledge of Persian Medicine in the future, the importance of Persian Medicine for patients, promoting the role of Persian Medicine specialists and creating diversity in the curriculum of medical students.